'Will the real writer please stand up': Flawed discursive self-presentation by Junot Diaz. (3rd December 2019) - Iyer, Sreedhevi
Abstract : As we enter the era of bullshitology, methods of evaluating 'authenticity' become even more necessary. Celebrity writers of color, like all writers, have to present themselves as themselves in literary discourse. However, due to the discursive tendency to pigeonhole authors of color, such authors instead construct a public persona to negotiate the paradoxical position they inhabit within the discourse. Junot Diaz, author of Pulitzer Prize-winning The Brief Wondrous Life of Oscar Wao, presents himself differently across different communicative contexts, by indexing existing metapragmatic stereotypes regarding the 'authentic' author. The results emerge as demonstrating Diaz's style-shifts that occur according to the size of the communicative contexts. The smaller the communicative platform, the more Diaz assuredly resists pigeonholing. Similarly, the larger the platform, the more Diaz capitulates towards pre-determined discursive labels. Such an outcome underlines the challenge contemporary authors face in order to remain viable and exert influence over prevailing cultural conversations.